Complete secondary choral music guide - Roach, Donald W. (Parker, 1989)
This book is divided into four parts: Administration of Junior and Senior High School Choruses; The Conductor and the Choral Score; Developing Choral Musicianship in Students; and Planning Rehearsals and Performances.